Development of Website-Based Information System to Facilitate Students in Finding Internship Opportunities - Hendrawan, Billy; Novianto, Rizki Alim; Sahara, Siti (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Internships play a crucial role in higher education by offering students valuable opportunities to gain professional experience and apply theoretical knowledge in a practical setting. However, the process of identifying and securing suitable internship positions can be challenging and time-consuming for both students and institutions. This research presents the development and implementation of a web-based information system designed to streamline the internship placement process and enhance accessibility for students. The proposed system addresses the challenges students face in navigating the myriad of internship opportunities across various industries and organizations. By leveraging web-based technology and a user-friendly interface, the platform facilitates the centralized listing of internships, enabling efficient search, filtering, and application processes. Through a comprehensive needs assessment and iterative design approach, the system incorporates features tailored to the specific requirements of students, academic institutions, and potential internship providers. Key functionalities include personalized profiles, customizable search filters, application tracking, and communication channels to coordinate internship placements. The system aims to improve the overall efficiency and effectiveness of the internship search process, ultimately supporting students in their career development and enhancing the quality of education